UMPSA as Quality Verification Centre (QVC) expands offering of Stand-Alone Micro-credentials - Mimi Rabita, Abd Wahit (UMPSA, 2025)
CYBERJAYA, 30 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to expand access to higher education in the country as it is entrusted with the role of Quality Verification Centre (QVC) to conduct quality verification assessments for Stand-alone Micro-credentials (SAMC) from Certificate level (T-3) to Doctorate level (T-8), subject to stipulated conditions.